2009
DOI: 10.1016/j.juro.2008.11.120
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of the PITX2 Gene Promoter Region is a Strong Independent Prognostic Marker of Biochemical Recurrence in Patients With Prostate Cancer After Radical Prostatectomy

Abstract: The prognostic information provided by PITX2 methylation adds significantly to currently used clinical variables such as Gleason grade and stage. Therefore, it could contribute to better counseling in patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 18 publications
4
100
1
Order By: Relevance
“…This cohort is described in more detail elsewhere. 15,16 For the validation of the prognostic power of the developed assay, leftover bisulfite-converted DNA from the EpiChip PITX2 validation study was used. 17 During that previous study, cohorts were recruited retrospectively from four sites under institutional review board approval.…”
Section: Cohorts and Patient Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…This cohort is described in more detail elsewhere. 15,16 For the validation of the prognostic power of the developed assay, leftover bisulfite-converted DNA from the EpiChip PITX2 validation study was used. 17 During that previous study, cohorts were recruited retrospectively from four sites under institutional review board approval.…”
Section: Cohorts and Patient Samplesmentioning
confidence: 99%
“…15 The previous study revealed that methylation at different levels could be found in most samples, and patient stratification into a high-risk and a low-risk group necessitated the use of a methylation cut-off. The cut-off had been defined with regard to an optimized clinical performance of the assay.…”
Section: Establishment and Verification Of A Methylation Cut-off For mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 We next examined the relationship between biochemical recurrence and the HM or LM groups. Univariate analysis of those in the HM group vs LM group revealed significant differences in disease-free survival (Figure 1d, log-rank P-value ¼ 0.043).…”
Section: Biochemical Progression-free Survivalmentioning
confidence: 99%
“…[7][8][9] In prostate cancer, hypermethylation of several genes has been associated with tumor aggressiveness in terms of clinical-pathological characteristics, biochemical recurrence, and/or mortality from prostate cancer. [10][11][12][13][14][15][16] Global hypomethylation, which may cause reactivation of the transcription of oncogenes and transposable elements and increases chromosomal instability and loss of imprinting, 17,18 has been less extensively investigated. We have recently conducted a systematic review of studies on prostatic tumor global hypomethylation and prostate cancer progression: 19 although studies were heterogeneous and mostly based on a limited sample size, global hypomethylation was reported to be associated with high Gleason score, advanced tumor stage, high pre-operative PSA, and presence of metastasis.…”
Section: Introductionmentioning
confidence: 99%